Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Unit Airport Operation Control Center (AOCC) di Bandar Udara Intetnasional Soekarno-Hatta Cengkareng - Muchammad Hamdani; Faiz Albanna (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2024)
This research was conducted with the aim of determining the influence of workload and work stress on the performance of the Airport Operation Control Center (AOCC) unit at Soekarno-Hatta Cengkareng International Airport. The population in this study were 41 members of the Airport Operation Control Center (AOCC) unit and the sample used for research was all members of the unit, namely 41 people. The research results show that there is a partial influence between workload on the performance of the Airport Operation Control Center unit with a calculated t value of 3.993. Job Stress also has a partial influence on performance with a calculated t result of 4.765. Apart from that, Workload and Work Stress have a partial influence on performance, namely with a calculated f result of 40.693.